The Analogy of Shadow Economy and Officially Non-Observed Economy - Sakalauskaitė, Rūta (Socialiniai tyrimai, 2019)
The study examines the analogy of the concepts of shadow economy and non-observed economy. This study is relevant due to the fact that the studies related to shadow economy face the diversity of concepts: it seems that the same phenomenon – companies’ hidden activity – is named differently in various sources. In scientific literature, companies’ hidden activity is commonly named as a ‘shadow economy’ (Enste, 2015, 2018; Gaspareniene, et al., 2014; Goel, et al., 2019; Koufopoulou, et al., 2019; Medina and Schneider, 2018; Novkovska, 2019; Remeikienė, et al., 2017; Sauka and Putnins, 2019; Schneider, 2018a, 2019; Williams and Horodnic, 2015; Zaman and Goschin, 2015). Meanwhile, official statistical institutions, e.g. Statistics Lithuania, Eurostat, World Bank, Organization for Economic Co-operation and Development, use other term to define companies’ hidden activity, i.e. ‘non-observed economy’ (European Commission, International Monetary Fund, Organisation for Economic Co-operation and Development, United Nations, World Bank, 2009; Juškienė, et al., 2004; Lietuvos statistikos departamentas, 2016, 2017). Taking into account that both of these concepts are used in the same context, it can be assumed that the concepts of shadow economy and non-observed economy are identical. However, in order to accept or reject this statement, it is essential to analyze in detail the object of the study – the concepts of the shadow economy and the non-observed economy. Therefore, the purpose of this study is to structure the concepts of shadow economy and non-observed economy and to identify their similarities and differences. It is done by using the following method: the study of concepts is based on a comparative analysis of the types of shadow economy and the areas of non-observed economy. Due to the complexity of economic processes, shadow economy and non-observed economy cover many fields. The types of shadow economy concept which is defined by the author are the following: • The underground economy which covers market output (e.g. undeclared income from legal activities, salaries paid in envelopes, concealed income, concealed value added or other taxes) concealed by legal operators. • The illegal economy covers the production of illicit operators (e.g. drug trafficking, illegal alcohol production, smuggling). • The informal economy covers market and private use output of units that have no obligation to register their activity (e.g. own-use production of households, auxiliaries). Correspondingly, the areas of non-observed economy concept which is used by official statistical institutions are the following: • The underground economy – a legal manufacturing activity that is deliberately concealed from the authorities due to tax evasion, safety at work or other non-compliance. • The illegal economy – the manufacturing activity of goods and services that is prohibited by law or carried out by unauthorized manufacturers. • The informal sector – manufacturing activities of unregistered households or unincorporated enterprises with non-registered employees, that produce market output. • The household production for own final use – the productive activity of households producing goods and services capitalized within the same households. Summarizing the shadow economy concept which is defined by the author and non-observed economy concept which is used by official statistical institutions, it can be stated that although the essence of the shadow economy and non-observed economy is the same, these concepts are not analogous. Thus, the assumption done at the beginning of this study (that the concepts of the shadow economy and non-observed economy are identical) is rejected. The similarity between the concepts of shadow economy and non-observed economy is related to the fact that both of them include market processes that violate legal regulation and adversely affect tax revenue and financial interests of the state, where official institutions are not informed about such activity. In addition to the similarity of the analyzed concepts, shadow economy as well as non-observed economy include underground, informal, illegal economies and production for own final use. The fundamental difference of the analyzed concepts is that shadow economy does not include statistical inaccuracies, but statistical inaccuracies are included in non-observed economy. Basically, statistical inaccuracies are defined as relevant information that is not taken into account due to weaknesses in the statistical surveys. To sum it up, shadow economy researchers who rely on non-observed economy data published by official statistical institutions, should pay attention to the treatment of statistical inaccuracies. Theoretically, if the part of statistical inaccuracies in non-observed economy is insignificant, then non-observed economy can be identified as the shadow economy. However, in order to ensure the quality of studies, in practice it is recommended to indicate to which specific types of shadow economy or areas of non-observed economy researchers refer to in their studies.